High school students' optimism, procrastination, and learning task outcomes - Magno, Marjorie M. (2007)
This study aimed to understand the relationship among optimism, procrastination and learning task outcomes of high school students.Sixty-five third year high school students from a medium-sized public school in Metropolitan Manila were administered a questionnaire that contained parts adapted from the Academic Attribution Style Questionnaire (AASQ) and the Procrastination Assessment Scale Students (PASS) as well as questions on their learning task outcomes. It was found that students are optimistic in the way they explain bad academic events. Optimistic people are less inclined to procrastinate. Assessments in school should be coupled with efforts to understand student's rationalization of their successes and failures. Future studies can investigate other variables such as teacher attributes, parental and peer influence, and student's study habits and time management.